Paleoclimatic and archaeological evidence from Lake Suches for highland Andean refugia during the arid middle-Holocene. (February 2019) - Vining, Benjamin R; Steinman, Byron A; Abbott, Mark B; Woods, Arielle
Severe aridity during the mid-Holocene, ca. 8.0–4.0 kyr BP, led to extreme ecological stress in the tropical Andes. Here, we report paleolimnological and archeological data from Lake Suches in southern Peru (70° 24' 12" W, 16° 55' 35" S) spanning 13.6–4.4 kyr BP. Integrated paleoclimate and archeological data reveal that moisture was locally available and the basin served as an ecological refugium throughout the mid-Holocene. Mid-Holocene aridity was established no later than 7.2 kyr BP, with maximum aridity ca. 5.5–4.8 kyr BP. However, water levels in Lake Suches were sustained throughout peak middle-Holocene aridity, even as other systems desiccated. Isotopic enrichment of water in Lake Suches (δ 18 Olake ) and extensive wetlands (δ 18 Obofedal ) surrounding the lake indicate prolonged residence time. These reservoirs, combined with elevation-linked hydrographic factors, mitigated mid-Holocene net decreases in atmospheric moisture. Archeological data from Suches indicate successive population increases beginning ca. 11.0–9.8 kyr BP as drier but more stable early Holocene conditions were established regionally. Population maxima in Suches during the mid-Holocene/mid-Archaic period ca. 9.0–7.0 kyr BP coincide with peak aridity in the Titicaca and Atacama systems, as well as documented archeological hiatuses in these regions. Population decreases coincide with peak aridity recorded in Lake Suches ca. 6.0–5.0 kyr BP, but the basin was never fully abandoned. Evidence for refugial microenvironments is key to understanding the persistence of human populations and other endemic Andean flora and fauna during the highly adverse climates of the middle-Holocene. We outline several mechanisms which likely explain the formation of refugia linked to bofedales and hydrographic characteristics of Suches. Understanding refugial dynamics will be key to understanding the effects of past climatic change, as well as addressing current warming and decreased precipitation trends in the tropical Andes.